2008
DOI: 10.1146/annurev.ecolsys.39.110707.173426
|View full text |Cite
|
Sign up to set email alerts
|

Pandora's Box Contained Bait: The Global Problem of Introduced Earthworms

Abstract: Introduced exotic earthworms now occur in every biogeographic region in all but the driest or coldest habitat types on Earth. The global distribution of a few species (e.g., Pontoscolex corethrurus) was noted by early naturalists, but now approximately 120 such peregrine species are recognized to be widespread from regional to global scales, mainly via human activities. Species adapted to human transport and to colonization of disturbed habitats are most widespread and are the principal invasive species. We id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
211
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(224 citation statements)
references
References 111 publications
3
211
0
5
Order By: Relevance
“…Impacts belowground or underwater are not as easily recognized as those aboveground. Landscapes overwhelmed by kudzu vines are striking, whereas disruption of soil organisms and processes by introduced earthworms did not attract significant attention until research revealed they can transform North American forests [65]. Similarly, direct threats to endangered endemic or charismatic species attract attention, whereas gradual changes in abundance and distribution of common species or ecological properties tend to pass unnoticed.…”
Section: From Long-term Management To Restorationmentioning
confidence: 99%
See 1 more Smart Citation
“…Impacts belowground or underwater are not as easily recognized as those aboveground. Landscapes overwhelmed by kudzu vines are striking, whereas disruption of soil organisms and processes by introduced earthworms did not attract significant attention until research revealed they can transform North American forests [65]. Similarly, direct threats to endangered endemic or charismatic species attract attention, whereas gradual changes in abundance and distribution of common species or ecological properties tend to pass unnoticed.…”
Section: From Long-term Management To Restorationmentioning
confidence: 99%
“…Causing massive tree death in Australia and California with wide-ranging impacts above-and belowground [92] Earthworms In deglaciated parts of North America lacking native worms, causing loss of organic matter, nutrient mineralization, enhanced plant invasion, loss of rare native species, and altered soil invertebrate communities [65] Predatory flatworm (Arthurdendyus triangulatus)…”
mentioning
confidence: 99%
“…However, the effects of invasion by these invertebrates on community and ecosystems aboveground or belowground has been explored in few studies (Cameron et al 2016), with the exception of invasive earthworms which have been subjected to substantial research effort over the past two decades (reviewed by Bohlen et al 2004;Hendrix et al 2008). For example, burrowing earthworms have been introduced to many North American forests that lack a native earthworm fauna (due to their elimination by Pleistocene glaciations), and thereby introduce a novel disturbance that has wide-ranging ecological impacts ( Fig.…”
Section: Invasive Belowground Consumersmentioning
confidence: 99%
“…For example, burrowing earthworms have been introduced to many North American forests that lack a native earthworm fauna (due to their elimination by Pleistocene glaciations), and thereby introduce a novel disturbance that has wide-ranging ecological impacts ( Fig. 3f; Hendrix et al 2008). Belowground effects include homogenization of soil physical structure, stimulation of soil microbial activity and greater mineralization of nutrients, and loss of organic matter (Bohlen et al 2004).…”
Section: Invasive Belowground Consumersmentioning
confidence: 99%
“…While the extent to which introduced earthworms have colonised natural sites is poorly known, results from Dlinza Forest Nature Reserve in Eshowe and from a recent survey of Queen Elizabeth Park, in Pietermaritzburg, highlighted that even at less disturbed sites introduced taxa can be more common than native taxa (Plisko 2000;Nxele 2012). It remains to be seen whether introduced earthworms are having important economic or ecological impacts in South Africa, but introduced earthworms have had major detrimental effects in several locations around the world (Hendrix et al 2008), particularly in areas where earthworms were not previously present (e.g. islands, or areas post-glaciation).…”
Section: Introductionmentioning
confidence: 99%